THE USE OF TEAM GAME TOURNAMENT TO IMPROVE STUDENTS’ ELT CLASSROOM INTERACTION AND READING COMPREHENSION IN RELATION TO SELF-EFFICACY - Gani, H. Ruslan Abdul (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2019)
This research is aimed to find out the implementation of Team Game Tournament to improve studentsâ€™ classroom interaction and reading comprehension viewed from self-efficacy. The subject of this study was 30 students at second grade students of SMPN 5 Kopang. Which consists of 14 males and 16 females. This study was classroom action research (CAR) with two cycles, each cycle consists of four steps: planning, acting, observing and reflecting. The first cycle was focused on the studentsâ€™ classroom interaction. Meanwhile, the second cycle was oriented to solve the studentsâ€™ improvement of reading comprehension. The data gathering used reading test, observation sheet, and questionnaires and analyzed by using quantitative and qualitative approach. The result of the questionnaire showed the students score in the first cycle was 16.86 or 56% and the second cycle showed the students’ score was 27.10 or 90.3% indicating the target of 75 of the minimum criterion has been achieved, it means that the action was stopped in the cycle 2. In other words, the studentsâ€™ classroom interaction and reading comprehension in relation to self-efficacy was improved by implementing team game tournament (TGT) for the eighth-grade students of SMPN 5 Kopang.